2023
DOI: 10.3390/diagnostics13071349
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a ddPCR Commercial Assay for the Absolute Quantification of the Monkeypox Virus West Africa in Clinical Samples

Abstract: Background: Monkeypox virus (MPXV) is a double-stranded DNA virus belonging to the orthopoxvirus genus in the family Poxviridae. Distinct clades are identified: the clade I belonging to the Central African (or Congo Basin) clade and the subclades IIa and IIb belonging to the West African clade. Here, a commercial droplet digital PCR (ddPCR) assay was evaluated for the quantification of the MPXV West Africa clade in clinical samples. Methods: The ddPCR reaction was assessed as a duplex assay using RPP30 as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…To determine the sensitivity of this assay, different copy numbers of MPXV DNA were used as the template. MPXV DNA was diluted to 10 3 copies, 10 2 copies, 10 copies, and 1 copy as absolute quantified by digital PCR 27 (Supporting Information S3: Figure S3A). Results showed that all four sets of primers and probes were able to detect MPXV DNA as low as 1 copy (Figure 1D).…”
Section: Specificity and Sensitivity Of The Raa-lf Systemmentioning
confidence: 99%
“…To determine the sensitivity of this assay, different copy numbers of MPXV DNA were used as the template. MPXV DNA was diluted to 10 3 copies, 10 2 copies, 10 copies, and 1 copy as absolute quantified by digital PCR 27 (Supporting Information S3: Figure S3A). Results showed that all four sets of primers and probes were able to detect MPXV DNA as low as 1 copy (Figure 1D).…”
Section: Specificity and Sensitivity Of The Raa-lf Systemmentioning
confidence: 99%